2021
DOI: 10.1002/alr.22874
|View full text |Cite
|
Sign up to set email alerts
|

Nasal endoscopy, room filtration, and aerosol concentrations during live outpatient encounters: a prospective, case‐control study

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic has highlighted safety concerns surrounding possible aerosol‐generating procedures, but comparative data on the smallest particles capable of transmitting this virus remain limited. We evaluated the effect of nasal endoscopy on aerosol concentration and the role of a high‐efficiency particulate air (HEPA) filter in reducing aerosol concentration. Methods Otolaryngology patients were prospectively enrolled in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“… 31 It is important to note these findings are specific to the particular HEPA filter used in the study along with other office characteristics such as room size and temperature. 31 Nonetheless, these results do indicate that HEPA incorporation can facilitate decreased room turnover time and protect both patients and clinical team members from potentially aerosolized viral particles.…”
Section: Decreasing Viral Transmission Riskmentioning
confidence: 94%
See 3 more Smart Citations
“… 31 It is important to note these findings are specific to the particular HEPA filter used in the study along with other office characteristics such as room size and temperature. 31 Nonetheless, these results do indicate that HEPA incorporation can facilitate decreased room turnover time and protect both patients and clinical team members from potentially aerosolized viral particles.…”
Section: Decreasing Viral Transmission Riskmentioning
confidence: 94%
“…30 Naturally, clinicians have sought avenues to improve air filtration, resulting in the incorporation of high-efficiency particulate air (HEPA) filters in numerous otolaryngology clinics. 30 , 31 Gill and colleagues found that HEPA incorporation into their clinics resulted in up to a 700% increase in clinical productivity per hour, as a result of decreased room turnover time. 30 They note that HEPA incorporation resulted in return of aerosol concentrations to baseline significantly faster.…”
Section: Decreasing Viral Transmission Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of these guidelines indiscriminately can rapidly escalate healthcare costs and increase the number of procedure downtimes unnecessarily. A recent prospective study utilizing particle sizers with an aerosol monitor showed no difference in aerosol generation and concentration between the use of nasal endoscopy without debridement and no use of endoscopy (95% CI [−0.11 to 2.14], P = 0.12), as well as between nasal endoscopy with debridement and no endoscopy (95% CI [−1.76 to 0.17], P = 0.36) [21]. This reinforces that standard infection control precautions can be taken with nasal endoscopy in at-risk patients, without the need for additional costly equipment such as powered air purifying respirators which are often used in high-risk AGPs.…”
Section: Coronavirus Disease 2019mentioning
confidence: 99%